STUDI KASUS IMPLEMENTASI METODE RESITASI PADA PEMBELAJARAN FIKIH PESERTA DIDIK KELAS XI.3 MAN 1 KOTA MAKASSAR - Ichsan, Muhammad; Khalisah Latuconsina, Nur; Rusmin B, Muhammad; Ruhaya, Besse; Iqbal, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research to describe the planning, implementation, and evaluation of the recitation method, as well as to identify the supporting and inhibiting factors in the implementation of the recitation method in Fiqh learning at MAN 1 Makassar City. This study employed a qualitative approach with a case study research design. Data were collected through interviews, observations, and documentation, and then analyzed through data reduction, data display, and conclusion drawing and verification. Data validity was ensured through triangulation techniques.The results of the study indicate that the planning stage of the recitation method begins with determining learning objectives and selecting learning materials in accordance with the Fiqh textbook. The implementation of the recitation method is carried out through the Problem-Based Learning (PBL) model, supported by lecture and question-and-answer methods, by connecting students’ understanding with the learning materials. Evaluation is conducted through several stages, including assigning tasks, conducting question-and-answer sessions, and teacher self-evaluation during the implementation of the recitation method.The supporting factors include the integration of various learning models, strategies, methods, techniques, and tactics, the availability of learning facilities and infrastructure, and moral support from the school. Meanwhile, the inhibiting factors include limited instructional time, classroom conditions, and low student attendance. The implications of this study show that the recitation method can help students become more active, responsible, and able to understand Fiqh materials more easily through activities such as summarizing, memorization, observation, and interviews.